Entrepreneurship education : experiments with curriculum, pedagogy and target groups - Manimala, Mathew J., 1950-; Thomas, Princy (Springer, 2017)
"The book provides an overview of developments in the field of entrepreneurship education, with special reference to global perspectives on innovations and best practices, as well as research in the emerging economy context. It focuses on various experiments in curriculum design, review and reform in addition to the innovative processes adopted for developing new content for entrepreneurship courses, in many cases with an assessment of their impact on students' entrepreneurial performance. Further, it discusses the pedagogical methods introduced by teachers and trainers to enhance the effectiveness of students' learning and their development as future entrepreneurs. It explains the various initiatives generally undertaken to broaden the scope of entrepreneurship education by extending it beyond regular students and offering it to other groups such as professionals, technicians, artisans, war veterans, and the unemployed. The book is a valuable resource for researchers and academics working in the field of entrepreneurship education as well as for trainers, consultants, mentors and policy makers."--Publisher's description.